(NiSTORIQ sOWETSKOGO sO@ZA (B:s (NW (B2-(NH TOMAH (B/s (Nt(B. 1.,s (NoT REWOL@CII DO wTOROJ MIROWOJ WOJNY(B. (NlENIN I sTALIN(B. 1917 - 1941 (NGG(B.s - (NbOFFA(B, (NdVUZEPPEs; (NbOFFA(B, (NdVUZEPPEs; (NaMBARCUMOW(B, (Ne(B. (Na(B.,s; (NlEWIN(B, (Ni(B. (Nb(B.,s ((NmOSKWA (B:s (NmEVDUNARODNYE OTNO[ENIQ(B,s, 1990)
(NpERWYM TOM WKL@^AET SOBYTIQ OTE^ESTWENNOJ ISTORII (B1917 - 1941 (NGODOW(B.s
(NuKAZ(B.: (NS(B. 619 - 625s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NlENIN w(B. (Ni(B.s; (NkERENSKIJ a(B. (Nf(B.s; (NkORNILOW l(B. (Ng(B.s; (NtROCKIJ l(B. (Nd(B.s; (NzINOWXEW g(B. (Ne(B.s; (NkAMENEW l(B. (Nb(B.s; (NbUHARIN n(B. (Ni(B.s; (NsTALIN i(B. (Nw(B.s; (NmOLOTOW w(B. (Nm(B.s; (NkAGANOWI^ l(B. (Nm(B.s; (NkIROW s(B. (Nm(B.s; )Qæ(NSTORÆQs)E -- )Qæ(NSTORÆQ srsrs)E; (NDRUGA SW)QÆTOWA WÆJNAs)E; )QÆ(NNTERNACÆONALs)E; (Nneps; (NB)QÆLX[OWIZMs)E; (NW)QÆJSXKOWIJ KOMUNÆZMs)E; (NGROMADQNSXKA W)QÆJNAs)E; )QÆ(NEDUSTRÆALÆZACÆQs)E; (NKOLEKTIW)QÆZACÆQs)E; (NKOLGOSPIs; (NREWOL@C)QÆQs)E; (NPROMISLOW)QÆSTXs)E; (NSTAL)QÆNÆZMs)E; (NSTAHANOWC)QÆs)E